Estudo da corrosão atmosférica do aço AISI 1020 usando a técnica de ruído eletroquímico e microscopia óptica - Fraga, Eduardo Fagiani (Universidade Federal de São Carlos, 2019)
The objective of this work was to study the corrosion of AISI 1020 exposed in an atmosphere containing acetic acid (HAc) vapor. Electrochemical noise (RE) oscillations and surface micrographs of the samples were obtained simultaneously during the corrosion process for 2000 s. A potentiostat/galvanostat was used to acquire the RE signals. Two identical AISI 1020 steel electrodes were used as working electrodes and another AISI 304 steel electrode as a pseudo-reference. For electrochemical measurements, a sealed glass cell saturated with HAc vapor was used. The cell has a flat bottom which has been adapted in an optical microscope (MO) to obtain steel surface images at 6 frames/min rate. Atmospheres formed from solutions containing 0.0%, 1.0%, 50.0% and 100% (V/ V) HAc showed different types of corrosive processes indicating different corrosion mechanisms. For solutions containing 1.0% (V/V), 50.0% (V/V) and 100% HAc the current transient amplitudes were in the order of 9.2 pA, 50.0 pA, 62.0 pA and 57.0 pA respectively. The results were analyzed by Wavelet Transforms (TO) and the results were organized in an energy distribution diagram (EDP) where the energies are arranged in 8 decomposition levels (d1-d8). For atmospheric experiments using solutions containing 1.0% HAc the energy distribution is concentrated at the highest levels (d5-d8) where the process is characterized by localized corrosion. This information is confirmed by the images obtained in situ, which showed the formation of pits. The EDP data for the experiments performed from 50.0% HAc solutions showed a concentrated energy distribution at the ends of the diagram (d1 and d8). In this experiment, through the obtained images it is possible to notice that, after the steam condensation, there is a generalized corrosion formation on the electrode surface followed by the formation of corrosion products. However, in an exact simulation with the same conditions as above, the electrode surface was sanded and thus it was observed that pitting also occurred. Finally, experiments using 100% HAc solutions showed an increase in the concentration of the relative energy distribution at levels d1 and d2 and a smaller relative energy distribution for the other levels. In situ images show more intense corrosion after the initial 700 s of the experiment. With the successful analysis, localized corrosion and generalized corrosion were contacted. The use of the RE technique combined with TO and OM proved to be effective in a short time to evaluate and classify the corrosive process.
Study of atmospheric corrosion of AISI 1020 steel using the technique of electrochemical noise and optical microscopy
Keywords: Corrosão atmosférica; Ácido acético; Ruído eletroquímico; Microscopia óptica; Transformada de ondaletas; Corrosion; Atmospheric; Acetic acid; Electrochemical noise; Optical microscopy; Wavelet transform; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA